2016
DOI: 10.1002/cncr.29868
|View full text |Cite
|
Sign up to set email alerts
|

Psychological morbidities in adolescent and young adult blood cancer patients during curative‐intent therapy and early survivorship

Abstract: BACKGROUND: Adolescents and young adults (AYAs) with cancer face unique psychosocial challenges. This pilot study was aimed at describing the prevalence of psychological morbidities among AYAs with hematologic malignancies during curative-intent therapy and early survivorship and at examining provider perceptions of psychological morbidities in their AYA patients. METHODS: Patients aged 15 to 39 years with acute leukemia, non-Hodgkin lymphoma, or Hodgkin lymphoma who were undergoing curative-intent therapy (on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 33 publications
1
53
2
2
Order By: Relevance
“…Similar to recent studies based on self‐report questionnaires, we found moderate and severe symptoms of anxiety and/or depression in more than a quarter of AYAs with cancer. In both our and the Muffly et al study, the screening instrument used revealed that more patients had increased depression scores than they did increased anxiety scores. Our CIDI‐O results showed a significantly lower prevalence rate of mood disorders than the PHQ‐9 results did, a phenomenon that is certainly due to the differing nature of those instruments (questionnaire to detect some selected symptoms vs clinical interview to detect psychiatric diagnosis).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar to recent studies based on self‐report questionnaires, we found moderate and severe symptoms of anxiety and/or depression in more than a quarter of AYAs with cancer. In both our and the Muffly et al study, the screening instrument used revealed that more patients had increased depression scores than they did increased anxiety scores. Our CIDI‐O results showed a significantly lower prevalence rate of mood disorders than the PHQ‐9 results did, a phenomenon that is certainly due to the differing nature of those instruments (questionnaire to detect some selected symptoms vs clinical interview to detect psychiatric diagnosis).…”
Section: Discussionmentioning
confidence: 98%
“…Existing research shows that AYA cancer survivors have a worse quality of life (QoL) than their general population peers, as well as specific problems in areas such as fertility, sexuality, career, and psychological well‐being. The majority of the few studies who examine psychological distress of AYAs with cancer have found that every fourth patient exceeds distress cutoff values during and after medical treatment . Furthermore, AYAs with cancer who have completed medical treatment are more distressed than age‐matched healthy controls .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, AYA survivors may avoid care because it would require missing work and lower their income, making it difficult to pay household bills. Indeed, in a study of AYA cancer survivors receiving financial assistance grants, 92% of the financial support provided was to support non‐medical costs, of which rent/mortgage accounted for 62% . Such findings suggest that AYA need additional support in order to maintain an appropriate income while receiving recommended care, particularly in settings without universal healthcare …”
Section: Major Challenges Faced By Aya Cancer Survivorsmentioning
confidence: 99%
“…22 In a cohort of hematologic malignancy survivors that used semistructured interviews, 23% met criteria for anxiety, 28% met criteria for depression and 13% met criteria for PTSS. 23 In a sample of Australian AYA’s, almost half were classified as being above the cutoff score for PTSS. 24 FOR is also common in young adult cancer survivors.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%